Strategic redundancy implementation : re-focus, re-organise and re-build - Stevens, Madeleine (Routledge, 2022)
"Redundancy, restructuring, downsizing. There are few, if any, other management books on this important topic, and yet the pace of redundancies has only accelerated in recent years. Coupled with this, many companies that implement redundancies as a cost-cutting exercise often fail to achieve their goal. Whilst viewed as an uncomfortable topic by many, guidance on how to implement a redundancy programme that is fair, proportionate and ultimately leads to improved organizational performance has never been more needed. This book fills this important gap. It takes the reader through a redundancy implementation strategy - Re-Focus, Re-Organise and Re-Build - that incorporates the key aspects of planning and analysis, fairness and justice, and preparing management for redundancy implementation through training. What will your communications include? What will be your strategy for implementation? What training does your management need? Various helpful templates are included for employee consultation, communication and training. The book will be invaluable for business managers, HR professionals, employee representatives and HR students"--